G368 DQ typing is effective in coeliac disease screening in children and young people with down syndrome in South East Scotland. (27th April 2016) - Sumner, C; Veerasamy, G; Clegg, S; Barlow, H; Comrie, A; Forgan, M; Mitchell, R; Gillett, P
Abstract : Aim: The association between Down syndrome (DS) and coeliac disease (CD) was first described in 1975. 1 Screening programmes for CD have utilised DQ typing in a number of studies 2, 3 but new guidance from the British Society of Paediatric Gastroenterology Hepatology and Nutrition (BSPGHAN) 4 suggested that it is should be a key part of assessment of all patients with DS. A negative DQ 2.5, 2.2 or 8 test, in a patient would essentially rule CD out and exclude them from further testing. We aimed to 'road test' the new BSPGHAN guidelines to assess their utility in clinical practice. Subjects: We looked at patients with DS aged 18 and under in our region between October 2014 and October 2015. Methods: Families with children with DS aged 18 and under in our area were contacted with an information leaflet about CD and offered testing for CD, in particular, coeliac disease genetic testing with DQ typing. Anti-TTG antibodies were measured and DQ 2.5. 2.2 and 8 typing was performed. Results: 48 patients (27 male and 21 female) were screened. The age range tested was 0.2–18.5 years, with a median age of 6 years. Overall 47.7% were DQ negative (Figure 1 ). No patients were found to be positive on anti-TTG testing. Figure 2 shows the breakdown of DQ types in the study. We were able to risk stratify those who were positive, (Figure 3 ) according to a recent position paper 1 . Conclusion: DQ typing is very effective in excluding children with DS from the need for further screening for CD (in nearly 50% of cases). This can be performed at the earliest opportunity in any child and should be accepted as a standard of care across the UK. All patients with the diagnosis of CD should be screened as future therapy is designed for patients with DQ2.5. References: Bentley D. Pediatrics 1975; 56:131–3 Book L, Hart A, Black J et al .J Med Genet 2001; 98:70–4 Czizmadia GDS, Mearin ML, Oren A et al. J Pediatr 2000; 137:756–61 Murch S, Jenkins H, Auth M, et al .Arch Dis Child 2013;98(10):806–11 Tye-Din JA, Cameron DJS, Daveson J, et al . Internal Medicine Journal 2015; 45